2006
DOI: 10.1088/0953-8984/18/14/s03
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatics of DNA–DNA juxtapositions: consequences for type II topoisomerase function

Abstract: Type II topoisomerases resolve problematic DNA topologies such as knots, catenanes, and supercoils that arise as a consequence of DNA replication and recombination. Failure to remove problematic DNA topologies prohibits cell division and can result in cell death or genetic mutation. Such catastrophic consequences make topoisomerases an effective target for antibiotics and anticancer agents. Despite their biological and clinical importance, little is understood about how a topoisomerase differentiates DNA topol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 38 publications
0
32
0
Order By: Relevance
“…For example, a recent atomic model study has investigated several hooked DNA juxtapositions with different segment curvatures. 33 Naturally, the likelihood of the occurrence of various juxtapositions in real DNA conformations as well as their topological discrimination power would be affected by local and global persistence lengths and other aspects of DNA conformational energetics. The impact of these physical factors on our proposed topoisomerase mechanism remains to be ascertained in future work.…”
Section: Counting Conformations In Various Knot Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent atomic model study has investigated several hooked DNA juxtapositions with different segment curvatures. 33 Naturally, the likelihood of the occurrence of various juxtapositions in real DNA conformations as well as their topological discrimination power would be affected by local and global persistence lengths and other aspects of DNA conformational energetics. The impact of these physical factors on our proposed topoisomerase mechanism remains to be ascertained in future work.…”
Section: Counting Conformations In Various Knot Statesmentioning
confidence: 99%
“…Thus, we have succeeded in demonstrating that the hooked versus free hypothesis is viable, at least for the two-loop catenation/decatenation case, 30 even though the detailed manner in which this principle may apply to real DNA molecules remains to be elucidated by further experimental and theoretical efforts. 33 Our previous study considered the linking/unlinking of two loops without regard to the various knot states of the individual loops. 30 The results in that study correspond to conformational properties averaged over all possible knotted and unknotted two-loop configurations.…”
Section: Introductionmentioning
confidence: 99%
“…In another paper in this issue, Randall et al (2006), we examine the effect of counterions on the likelihood of two DNA helices juxtapositing. Counterions shield the negative charge of the phosphates on the DNA backbone and therefore allow a close approach of DNA helices.…”
Section: Importance Of Counterionsmentioning
confidence: 99%
“…A kinetic proofreading model that requires two separate topoisomerase-DNA collisions for segment passage and a model of interaction of the enzyme with three segment-interactions have been also proposed (Yan et al, 1999;Trigueros et al, 2004). Alternatively, it has been suggested that the topological information may be embodied in the local geometry of DNA crossings and that topoisomerases act at the hooked juxtapositions of the strands (Buck and Zechiedrich, 2004;Randall et al, 2006). Indeed, recent experimental studies support this view in showing that topoisomerase IV and DNA gyrase can discriminate the sign of supercoiled DNA on the basis of the geometry of the DNA crossovers (Crisona et al, 2000, Charvin et al, 2003, Stones et al, 2004Nöllmann et al, 2007;Corbett et al, 2005).…”
Section: From Crossover Geometry To Dna Topologymentioning
confidence: 99%